Heroes and victims : remembering war in twentieth-century Romania - Bucur, Maria, 1968- (Bloomington : Indiana University Press, 2010)
Heroes and victims explores the cultural power of war memorials in 20th-century Romania through two world wars and a succession of radical political changes -- from attempts to create pluralist democratic political institutions after World War I to shifts toward authoritarian rule in the 1930s, to military dictatorships and Nazi occupation, to communist dictatorships, and finally to pluralist democracies with populist tendencies. Examining the interplay of centrally articulated and locally developed comme.
Memory traces: on local practices of remembering and commemorating -- Death and ritual: mourning and commemorative practices before 1914 -- Mourning, burying, and remembering the war dead: how communities coped with the memory of wartime violence, 1918-1940 -- Remembering the great war through autobiographical narratives -- The politics of commemoration in interwar Romania, 1919-1940: dialogues and conflicts -- War commemorations and state propaganda under dictatorship: from the crusade against Bolshevism to Ceausescu's cult of personality, 1940-1989 -- Everyone a victim: forging the mythology of anti-communism counter-memory -- The dilemmas of post-memory in post-Communist Romania.
Includes bibliographical references (pages 307-336) and index.
Print version record.
JSTOR
Keywords: Memorialization -- Romania -- History -- 20th century; Memory -- Social aspects -- Romania; War and society -- Romania; World War, 1914-1918 -- Social aspects -- Romania; World War, 1939-1945 -- Social aspects -- Romania; War memorials -- Social aspects -- Romania; Collective memory -- Romania; Romania -- History, Military -- 20th century; Commémorations -- Roumanie -- Histoire -- 20e siècle.; Guerre et société -- Roumanie; Guerre mondiale, 1914-1918 -- Aspect social -- Roumanie; Guerre mondiale, 1939-1945 -- Aspect social -- Roumanie; Monuments aux morts -- Aspect social -- Roumanie; Mémoire collective -- Roumanie; POLITICAL SCIENCE -- Peace; HISTORY -- Modern -- 20th Century; Collective memory; Memorialization; Memory -- Social aspects; Social aspects; War and society; Romania; 1900 - 1999; History; Military history